Adopting the Crowdsourcing in Activation Strategic Foresight for Leaderships Towards Managerial Reforming Strategies Selection A Suggested Study for Managerial Leadership - حسن علاء احمد (Journal of Economics and Administrative Sciences, 2019)
Abstract Environmental data (whether pre-emptive or responsive perspective) impose management theories, through of which the organization can accommodating the most influential variables. As the information and communication technologies with its different generations led to the activation of the community role in strategic decision making in organizations, in this context, the research problem focused on the following questions: Is it possible for the reform process to take place and to choose one of its alternatives by direct crowdsourcing? Is it possible that the process of reform and alternative selection through the crowdsourcing of the collective after the passage of strategic insight? , The importance of research has presented a practical methodology contributed by the field to modify to achieve the reform process with options that will provide financial and social costs, as well as time and confidence building with the local and international community and spreading the risk of reform between government and communities. The research sought to focus on the role of societies in administrative reform through the strategic foresight of the leaders, which widens the role of the societies to the participant and lead to the supervisory role, and explains the importance of leadership by its strategic dimension in extrapolating the indicators towards the societies towards the strategic alternative to reform. In order to address the problem and achieve the objectives’. The research were adopted two basic hypothesis the direct impact of the outsourcing of collective management reform strategies, and the second has an indirect impact of the crowdsourcing of collective management reform strategies through strategic foresight. The research tried to activation of community role in administrative reform by strategic foresight for leaderships which broadens the role of communities to a participant, pioneer and supervisory role. Adding to that, explanation the importance of leadership with its strategic leadership dimensions in extrapolation of indicators towards the strategic alternative to reform. The research was implemented in the office of Nineveh Province which included (40) of relevant managers from the community of (50) managers. So the sample percentage was (80%) of the original population. The researcher used the path analysis as appropriate statistical method. The most important conclusion of the research was “The validity of the model proved to be the first effect, it was made according to the surveyed field”. Furthermore, the researcher presented a set of recommendations that would activate the mechanisms of the proposed model in the surveyed field.